A novel somatic mutation achieves partial rescue in a child with Hutchinson-Gilford progeria syndrome. Issue 3 (5th December 2016) - Bar, Daniel Z; Arlt, Martin F; Brazier, Joan F; Norris, Wendy E; Campbell, Susan E; Chines, Peter; Larrieu, Delphine; Jackson, Stephen P; Collins, Francis S; Glover, Thomas W; Gordon, Leslie B
Abstract : Background: Hutchinson-Gilford progeria syndrome (HGPS) is a fatal sporadic autosomal dominant premature ageing disease caused by single base mutations that optimise a cryptic splice site within exon 11 of the LMNA gene. The resultant disease-causing protein, progerin, acts as a dominant negative. Disease severity relies partly on progerin levels. Methods and results: We report a novel form of somatic mosaicism, where a child possessed two cell populations with different HGPS disease-producing mutations of the same nucleotide—one producing severe HGPS and one mild HGPS. The proband possessed an intermediate phenotype. The mosaicism was initially discovered when Sanger sequencing showed a c.1968+2T>A mutation in blood DNA and a c.1968+2T>C in DNA from cultured fibroblasts. Deep sequencing of DNA from the proband's blood revealed 4.7% c.1968+2T>C mutation, and 41.3% c.1968+2T>A mutation. Conclusions: We hypothesise that the germline mutation was c.1968+2T>A, but a rescue event occurred during early development, where the somatic mutation from A to C at 1968+2 provided a selective advantage. This type of mosaicism where a partial phenotypic rescue event results from a second but milder disease-causing mutation in the same nucleotide has not been previously characterised for any disease.